2022
DOI: 10.18502/ijps.v17i4.10692
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Relation between Resilience, Locus of Control, Quality of Relationship and Pain Intensity with Dialysis Adequacy in Patients with Peritoneal and Hemodialysis

Abstract: Objective: Mental health in people with chronic diseases undergoes many changes due to conflict with the pain caused by the disease, which can have a reciprocal effect on the course and quality of the patient's treatment. The goal of the present study is to compare the correlation between locus of control, relationship quality, pain intensity and resilience with dialysis adequacy and laboratory indicators in peritoneal dialysis and hemodialysis patients. Method: This causal-comparative study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…[14][15][16] Peritoneal dialysis patients usually undergo catheterization surgery, a traumatic procedure that damages abdominal tissues and releases chemical substances like bradykinin, proteolytic enzymes, and serotonin, stimulating nerve endings and causing pain and discomfort. 17,18 Post-operative swelling and dull pain at the catheter exit site significantly impact the patient's psychological state and postoperative recovery. 19 Therefore, timely and effective measures to alleviate pain and adverse emotions are clinically significant.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Peritoneal dialysis patients usually undergo catheterization surgery, a traumatic procedure that damages abdominal tissues and releases chemical substances like bradykinin, proteolytic enzymes, and serotonin, stimulating nerve endings and causing pain and discomfort. 17,18 Post-operative swelling and dull pain at the catheter exit site significantly impact the patient's psychological state and postoperative recovery. 19 Therefore, timely and effective measures to alleviate pain and adverse emotions are clinically significant.…”
Section: Introductionmentioning
confidence: 99%
“…A 2001 study collected experiences from dialysis nurses regarding the importance of the therapeutic nurse–patient relationship and the benefits it can bring; it reported that better listening skills toward the persons being cared for, focusing on their life and history, allows for effective relationship building and helps to obtain useful information about the patients’ health status [ 11 ]. The nurses noted the importance of not rejecting emotions, even if negative, as in the case of angry or frustrated patients; they suggested encouraging the expression of this feeling in order to direct the patient’s attention to the goal they have to achieve instead of denying the presence of it [ 11 , 12 ]. Thus, it emerges how an effective therapeutic relationship between nurse and patient can also bring benefits to health care professionals who reported how they have been encouraged by their patients with whom they shared their feelings during a hard period of their private life [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%